Video-based teach-to-goal intervention on inhaler technique on adults with asthma and COPD: A randomized controlled trial. - Mohammad Samer Al-Kharouf; Mariam Hantash Abdeljalil; Nathir M Obeidat; Khaled Al Oweidat; Oriana Awwad (PLoS ONE, 2023)
Background Incorrect use of inhalers is a problem associated with poor patient outcomes. Despite improvement in the technique after verbal educations, this deteriorates over-time requiring re-enforcement through different educative strategies. This study aimed to assess the impact of a novel video-based teach-to-goal (TTG) educational intervention on: mastery of inhaler technique, disease control, medication adherence and disease-related quality of life (QoL) over-time among asthma and COPD patients. Methods This prospective, open-label, randomized controlled trial was registered in ClinicalTrials.gov: Identifier NCT05664347. After baseline assessment participants received either a verbal (control group) or a video-based (intervention group) TTG strategy. After 3-month the intervention was assessed for impact on the intended outcomes. Inhaler technique was assessed using standardized checklists, disease control using the Asthma control test and COPD assessment test respectively for asthma and COPD patients while adherence using the Morisky Green Levine scale. For QoL, the mini asthma quality of life questionnaire and the St. George respiratory questionnaire were used for asthmatic and COPD patients, respectively. Differences in outcomes between intervention-control groups were analyzed using either Chi-Square (X2)/Fisher Exact or Mann Whitney test. The impact of intervention on outcomes over-time was examined using either McNemar or Wilcoxon test. Results At baseline, intervention (n = 51) and control (n = 52) groups had comparable demographic/clinical characteristics. At follow-up, inhaler technique improved among intervention group compared to control group (93.4% vs 67%) and to baseline (93.4% to 49.5%), (P<0.05). Similarly, medication adherence ameliorated among the intervention group in comparison to control group (88.2% to 61.5%) and to baseline (88.2% to 66.7%), (P<0.05). In regards to disease control, results showed an amelioration among the intervention group compared to baseline (35.3% to 54.9%) (P<0.05). QoL scores improved significantly among asthma patients (intervention group) at follow-up vs baseline. Better scores were also observed for COPD patients compared to controls, (P<0.05). Conclusion Video-based (TTG) was effective in enhancing inhaler technique over time as well as improving disease control, medication adherence, and QoL. Trial registration ClinicalTrials.gov: NCT05664347. https://clinicaltrials.gov/ct2/show/NCT05664347.